2020
DOI: 10.1371/journal.pone.0229531
|View full text |Cite
|
Sign up to set email alerts
|

Frailty predicts surgical complications after kidney transplantation. A propensity score matched study

Abstract: Background and objective Surgical complications after kidney transplantation can lead to catastrophic outcomes. Frailty has been associated with important kidney transplantation outcomes; however, there are no studies assessing this measure of physiological reserve as a specific predictor of surgical complications in this population. Such an assessment was, therefore, the objective of the present study. Methods A total of 87 individuals aged � 18 years who underwent kidney transplantation between March 2017 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 39 publications
0
26
0
1
Order By: Relevance
“…Four studies reported data on the association between frailty and DGF for both frail and nonfrail patients. 25 , 27 , 28 , 32 All 4 studies defined DGF as the need for dialysis during the first 7 postoperative days. 19 Overall, frail patients had an increased risk of DGF compared with nonfrail patients (OR, 1.80; 95% CI, 1.1-3.0).…”
Section: Resultsmentioning
confidence: 99%
“…Four studies reported data on the association between frailty and DGF for both frail and nonfrail patients. 25 , 27 , 28 , 32 All 4 studies defined DGF as the need for dialysis during the first 7 postoperative days. 19 Overall, frail patients had an increased risk of DGF compared with nonfrail patients (OR, 1.80; 95% CI, 1.1-3.0).…”
Section: Resultsmentioning
confidence: 99%
“…High BMI level at the time of transplantation is associated with increased risk of posttransplant mortality, graft failure, delayed graft function, and other surgical complications 5‐7 . Low BMI levels have also been shown as a risk factor for diminished posttransplant outcomes, which in some cases may relate to frailty and sarcopenia 8‐11 . Cumulatively, there is a well‐established “J‐Shaped” curve characterizing risks associated with BMI for kidney transplant recipients.…”
Section: Introductionmentioning
confidence: 99%
“…In the first 24 hours after kidney transplantation, nursing actions aim to prevent complications and prioritize the continuous evaluation of general health status with noninvasive monitoring of vital signs and evaluation of the nursing team of 1 hour/1 hour in the first 12 postoperative hours, which allows early and appropriate interventions for each type of worsening. This period of great potential for hemodynamic instability, cardiovascular and neurological complications, important metabolic alterations and the need for replacement of parenteral fluids in large volumes that require intensive care for the maintenance of life (5,23,43,(44)(45)(46)(47)(48)(49).…”
Section: Resultsmentioning
confidence: 99%